360 Intrusions in a Miniature Volcano: Birth, Growth, and Evolution of an Analog Edifice - Derrien, Allan; Taisne, Benoit (Frontiers in Earth Science, 2019)
Volcanoes throughout the world have been monitored with complete geophysical data for no more than three decades, a relatively short time compared to their overall life. The consequence is that we lack a long observation of volcanic growth and behavior to get a more complete picture of the interaction between edifice stress state and magma transfer. Here we present the birth and evolution of a 83x83 cm analog model, where we reproduce for the first time volcanic growth over 360 successive intrusions (15 mL every half hour, at a rate of 3 mL/min) in an analog elasticity-dominated material (pigskin gelatine). Our model volcano started as a flat topography and ended 3.82 cm in height at the summit. It displayed cyclic eruptive patterns with alternating phases of eruptive and purely intrusive behavior. Alike to many intraplate volcanoes in nature, main dyke swarms produced in the experiment were disposed in a three-branched star pattern centered above the injection source (“volcanic rift zones”). Two radial sill networks, at source depth and edifice base, surrounded them. The interaction of edifice growth and magma transfer was dominated by long-term radial compressive stress building during dyke swarming and radial compressive stress release/compensation during sill emplacement. Near-surface stresses, deduced from the main orientation eruptive fissures and “dry” fractures, became more localised as the volcano grew. At the end of the experiment, the shallow stress field was interpreted as generally extensional radial at the summit, extensional tangential on the flanks, and compressive radial in distal areas.